Concentration profiling of a horizontal sedimentation tank utilising a bespoke acoustic backscatter array and CFD simulations. (8th June 2020) - Hunter, Timothy N.; Peakall, Jeff; Egarr, Darrell; Cowell, David M.J.; Freear, Steven; Tonge, Alastair S.; Horton, Lucy; Rice, Hugh P.; Smith, Iain; Malone, Kevin; Burt, David; Barnes, Martyn; et al.
Graphical abstract: Highlights: Characterisation of large-scale clarifier with OpenFOAM CFD & ultrasonic array. CFD correlated closely to sampled concentration profiles with glass dispersions. CFD under-predicted particle levels with calcite flocs, likely due to floc break-up. Acoustic array was successful at profiling clarifier with backscatter power method. Array was proven for high fidelity CFD validation data and process monitoring. Abstract: The performance of a pilot-scale horizontal sedimentation tank was characterised utilising computational fluid dynamics (CFD) and a bespoke ultrasonic backscatter array, for both spherical glass and flocculated calcite separation. The CFD simulation was developed in OpenFOAM, using algebraic slip and hindered settling models, in order to solve the transport of multiple particle size classes, enabled through a population balance approach. Simulations of concentration compared closely to samples for the glass dispersions, but under-predicted concentration with flocculated calcite (likely due to complexities from modelling floc break-up in the mixer). In comparison, the acoustic array measured the calcite concentration with a high degree of resolution, where in particular, evidence suspension mobilisation near the outlet was observed, due to recirculation. Overall, we demonstrate the performance and current limitations of large-scale CFD for complex floc systems, as well as the use of ultrasonics to significantly aid process understanding, through online monitoring of solid-liquid separations.